Macro-economic determinants of UK treasury bonds spread - Soh, Wei Chee; Cheng, Fan Fah (Center for Enhancing Knowledge, 2013)
This paper studies the relationship between eight macroeconomic determinants and the UK government bond yields. The paper also enhances the previous researches on relationship between macroeconomic factors and the gilts yields. The results show that only 1) short term interest rates have strong and negative impact on five-year, ten-year and twenty-year UK government bond yields. 2) The exchange rates have significant and positive relationship with five-year UK government bond yield. Whereas, the other macroeconomics variable have no impact on the yields and yield spreads of the UK government bonds.